1980
DOI: 10.1128/jb.144.1.200-204.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution and linkage of D-(-)-3-hydroxy fatty acids in Bacteroides species

Abstract: Two strains of Bacteroides asaccharolyticus and two strains of Bacteroides fragilis were analyzed for total fatty acid, total lipid fatty acid, and total bound fatty acid profiles. Extracted lipids and defatted cell residues were subjected to sequential alkaline and acid methanolyses to distinguish ester- and amide-linked fatty acids in each fraction. In the lipid fractions, all the ester-linked fatty acids were nonhydroxylated, whereas all of the amide-linked fatty acids were hydroxylated. In the nonextractab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Virtually all other saponifiable complex lipids hold fatty acids in an ester linkage. Mayberry reported that all 3-OH iC 17:0 recovered in Bacteroides fragilis and Bacteroides asaccharolyticus lipids was amide linked (20); however, the specific class or classes of complex lipids holding 3-OH iC 17:0 were not identified in this report. Preliminary work has also shown that 20 to 70% of the 3-OH iC 17:0 in lipid extracts from isolates of Porphyromonas gingivalis, a suspected periodontal pathogen, is in an amide linkage (data not shown).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Virtually all other saponifiable complex lipids hold fatty acids in an ester linkage. Mayberry reported that all 3-OH iC 17:0 recovered in Bacteroides fragilis and Bacteroides asaccharolyticus lipids was amide linked (20); however, the specific class or classes of complex lipids holding 3-OH iC 17:0 were not identified in this report. Preliminary work has also shown that 20 to 70% of the 3-OH iC 17:0 in lipid extracts from isolates of Porphyromonas gingivalis, a suspected periodontal pathogen, is in an amide linkage (data not shown).…”
Section: Discussioncontrasting
confidence: 59%
“…For determination of total hydroxy fatty acids, the remaining half of each tissue lipid extract was supplemented with 2 N HCl (0.5 ml) and heated overnight at 100°C (20). The sample was cooled, and 16 N KOH (0.37 ml) was added; this was followed by incubation at 100°C for 90 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nonextractable or bound fractions, the fatty acids appeared to be evenly divided between the ester-linked (alkali-labile) fatty acids, which were predominantly nonhydroxy acids, and the amide-linked (alkali-stable, acid-labile) fatty acids, which were predominantly hydroxy acids. The bound fatty acid fractions comprised approximately 10 mol% of the total cellular fatty acids, a situation not uncommon in bacteria (9,10).…”
mentioning
confidence: 99%
“…The fatty acid composition of each LPS preparation was determined by adding 3 jig of nonadecanoic acid (Sigma Chemical Co., St. Louis, Mo.) to LPS samples (1 mg) and then by hydrolysis in 4 N KOH (100°C, 4 h) (15,16). After adjusting the pH of hydrolysates to 1, free fatty acids were extracted with chloroform (three times, 1 ml each), and the pooled extracts were dried under N2 gas.…”
Section: Gamma Interferon Effects On Lps-stimulated Monocytesmentioning
confidence: 99%